Learner Autonomy Practices in English Language Teaching in EFL Context - Paudel, Jagadish (Journal of NELTA Gandaki, 2019)
Einstein says “I never teach my students. I simply provide the situations in which they can learn”. In line with this saying the learner autonomy (LA) approach provides learners with situations where they can learn independently in their own pace. This learner centered approach to teaching, emerged during the 1980s, aims at empowering learners by transforming responsibilities to them. This study aimed at exploring the practice level scenario of LA in English language teaching and learning. To this end, I employed the qualitative research design i.e. I observed teachers’ classes and conducted Focus Group Discussion (FGD) with the students. The information elicited from participants was transcribed, codified, categorized and finally themes were generated. The study revealed that, though the teachers and the students were affirmative towards LA, in a real sense, the majority of them did not adopt in English language teaching and learning. The classroom ritual is still teacher oriented. On the one hand, the teachers are still in the cockpit of pedagogy without providing any agency for the students. On the other hand, students' readiness for bearing responsibility of their learning was found weak. They preferred attachment to teachers without taking charge of learning.